Strawberry growth, development and diseases - Husaini, Amjad M.; Neri, Davide (CABI, 2016)
This book provides a broad, well-structured review of strawberries and their cultivation under current environmental conditions. Methods of strawberry cultivation have undergone many improvements, and this book covers aspects from plant propagation, architecture, genetic resources, breeding, abiotic stresses and climate change to evolving diseases and their control. The first chapter gives a general introduction to strawberry with some important statistics. It is followed by Section 1 on Genetics, Breeding and Omics, which contains five chapters. Chapters 2 and 3 discuss modern aspects related to available genetic resources and breeding for yield, quality and disease traits. The scope of metabolomics is discussed with special reference to white strawberry (Fragaria chiloensis subsp. chiloensis f. chiloensis) in Chapter 4. Chapter 5 is an interesting study on the transcriptomic profile of some key genes in relation to systemic acquired resistance, while chapter 6 discusses different aspects of genetic transformation in strawberry. Section 2 on Cultivation Systems and Propagation contains three chapters. These chapters discuss at length the plant growth, flowering, root growth and architecture, replant problems and plant propagation techniques. Section 3 on Disease and Stress Management contains six chapters dealing with biotic and abiotic stresses of strawberry. The first four chapters discuss traditional and emerging fungal diseases, their diagnosis and modern biointensive management strategies. Chapters 14 and 15 deal with the emerging challenges posed due to climate change and its impact on the changing magnitude and dimensions of abiotic stresses on strawberry. The book is aimed at those involved in strawberry research and development, and also to those who are interested in cultivation of strawberry for commercial gain.